Prevalence and Risk Factors of Anxiety and Depression in Rosacea Patients: A Cross-Sectional Study in China - Chen, Mengting; Deng, Zhili; Huang, Yingxue; Li, Ji (Frontiers in Psychiatry, 2021)
Rosacea is a chronic inflammatory skin disease characterized by facial redness and bothersome symptoms. It can exert significant psychological effects and impair the quality of life of patients. To investigate the prevalence and risk predictors of anxiety and depression in rosacea patients, we conducted a cross-sectional study in an outpatient setting. Consecutive patients completed a questionnaire, which included questions on sociodemographic information and severity of signs and symptoms; they also completed the Patient Health Questionnaire and the Generalized Anxiety Disorder scale. Disease burden was assessed using Dermatology Life Quality Index (DLQI), Willing-to-Pay, and Time trade-off. Multivariate analysis was conducted to determine the risk factors for anxiety and depression. A total of 774 patients completed the survey. The prevalence of anxiety was 53.9% (95% CI: 50.4–57.4%) and that of depression was 58.1% (95% CI: 54.7–61.6%). The factors associated with anxiety were age, gender, the need to make appearances at work, severity of self-reported symptoms, the number of rosacea signs and adaptive behaviors, and disease burden. Depression was associated with younger age, more severe self-reported symptoms, more adaptive behaviors, and higher disease burden. After adjusting for demographics, the risk of anxiety or depression increased in young patients who had severe self-reported symptoms, high DLQI scores, and many adaptive behaviors. Taken together, there is a high prevalence of anxiety and depression among Chinese rosacea patients. Younger rosacea patients who have more severe self-reported symptoms and higher disease burden are prone to anxiety and depression.